Selective protection of human liver tissue in TNF-targeting of cancers of the liver by transient depletion of adenosine triphosphate. - Timo Weiland (Public Library of Science (PLoS), 2012)
Background Tumor necrosis factor alpha (TNF) is able to kill cancer cells via receptor-mediated cell death requiring adenosine triphosphate (ATP). Clinical usage of TNF so far is largely limited by its profound hepatotoxicity. Recently, it was found in the murine system that specific protection of hepatocytes against TNF's detrimental effects can be achieved by fructose-mediated ATP depletion therein. Before employing this quite attractive selection principle in a first clinical trial, we here comprehensively investigated the interdependence between ATP depletion and TNF hepatotoxicity in both in vitro and ex vivo experiments based on usage of primary patient tissue materials. Methods Primary human hepatocytes, and both non-tumorous and tumorous patient-derived primary liver tissue slices were used to elucidate fructose-induced ATP depletion and TNF-induced cytotoxicity. Results PHH as well as tissue slices prepared from non-malignant human liver specimen undergoing a fructose-mediated ATP depletion were both demonstrated to be protected against TNF-induced cell death. In contrast, due to tumor-specific overexpression of hexokinase II, which imposes a profound bypass on hepatocytic-specific fructose catabolism, this was not the case for human tumorous liver tissues. Conclusion Normal human liver tissues can be protected transiently against TNF-induced cell death by systemic pretreatment with fructose used in non-toxic/physiologic concentrations. Selective TNF-targeting of primary and secondary tumors of the liver by transient and specific depletion of hepatocytic ATP opens up a new clinical avenue for the TNF-based treatment of liver cancers.